The Effect of Jati Belanda Leaves (Guazuma ulmifolia Lamk.) Ethanol Extract on Microscopic Features of Atherosclerotic Animal Modelâs Aorta - Permana, Ryan J.; Azaria, Cherry; Rosnaeni, Rosnaeni (Maranatha Christian University, 2016)
âJati Belandaâ leaves (Guazuma ulmifolia Lamk.) possesses antidyslipidemia effect and in this study we assessed the effect of